Performance Evaluation of Tween 60 Surfactant for EOR: Interfacial Tension Reduction and Microemulsion Formation - Pauhesti Pauhesti; Ridha Husla; Sri Feni Maulindani; Apriandi Rizkina Rangga Wastu; Nadira Cahya Sutikna; Lailatul Wastiyah; Ade Kurniawan Saputra (Scientific Contributions Oil and Gas, 2025)
Enhanced Oil Recovery (EOR) techniques are essential for maximizing crude oil extraction from mature reservoirs. Surfactant injection, particularly using surfactants such as Tween 60, has shown great potential in reducing interfacial tension (IFT) and enhancing oil recovery. This study evaluates the performance of Tween 60 for EOR applications, focusing on its aqueous stability, phase behavior, IFT reduction, and core flooding efficiency at temperatures of 60°C and 80°C. The research addresses a gap in the literature by examining the long-term stability and phase behavior of Tween 60 at these temperatures. Aqueous stability tests over seven days indicate that Tween 60 remains clear and stable at 60°C but becomes cloudy and unstable at 80°C. Phase behavior tests reveal that a 0.5% concentration of Tween 60 produces the largest middle-phase microemulsion (5.75% volume), forming a bicontinuous Winsor III microemulsion that enhances oil-water interaction. IF T tests using a spinning drop tensiometer show a reduction in IFT to 0.00525 dyne/cm. Core flooding tests confirm that surfactant injection contributes an incremental oil recovery of 8.33% beyond what was achieved by waterflooding without surfactant, increasing the total recovery factor from 62.5% to 70.83%. However, limitations such as the short testing period (14 days) and the use of a single type of oil (39 ° API) underscore the need for further research.